Cause Analysis and Enlightenment of Global Blackouts in the Past 30 Years - Yuan HU; Song XUE; Han ZHANG; Hua ZHANG; Xinxin FENG; Chenghui TANG; Yi LIN; Peng ZHENG (Zhongguo dianli)
Since 2019, Venezuela, Argentina, the United States, Indonesia, the United Kingdom, and other countries have successively experienced blackouts, and power grid security has become the focus of public attention. This paper sorted out 138 major blackouts in the past 30 years and found that after 2008, blackouts entered a period of high incidence, and major economies become the “severely affected areas”. Specifically, natural disasters accounted for 56% of those blackouts, and their scope of impact was relatively clear and controllable. management factors accounted for 31%, and they were easily accompanied by other inducing factors. These global and systematic influences may endanger the energy security of the entire country and region. Emergencies or human error accidents accounted for 10%. In addition, cyber-attacks became an emerging cause, accounting for 3%, and it was concealed, complex, and difficult to defend, easily leading to huge physical damage. After an in-depth analysis of the causes for the four types of blackouts, this paper puts forward measures and suggestions to prevent blackouts in China in light of the current development of China’s power grid.